1997
DOI: 10.1021/la970406y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Thermochromic Carbohydrate-Modified Polydiacetylene Thin Films

Abstract: Polymerized thin films based on polydiacetylenes (PDAs) undergo distinct color transitions that lend themselves to applications in biosensing, surface modification, nonlinear optics, and molecular electronics. The mechanism of the thermochromic blue to red color transition of PDA thin films was investigated at the molecular level using atomic force microscopy and at the macroscopic level with visible absorption and Fourier transform infrared spectroscopy. The thermochromic transition temperature is found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
157
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 38 publications
14
157
1
Order By: Relevance
“…[28][29][30] However, recent infrared spectroscopy and AFM studies of PDA films suggest that the side chains of "red phase" PDAs induced by thermal treatment are in an equally or more ordered conformation than those in "blue phase" PDAs. 7,8 A compromised explanation suggests that the alkyl side chains in the "red phase" remain in an ordered conformation, with only a slightly different packing mode from the "blue phase". 31 More recent investigation of the temperature dependence of visible absorption spectra and the electron diffractions of PDA films revealed that the electronic natures of the PDAs are strongly dependent on their resonance backbone structures as well as the stacking of the main chains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] However, recent infrared spectroscopy and AFM studies of PDA films suggest that the side chains of "red phase" PDAs induced by thermal treatment are in an equally or more ordered conformation than those in "blue phase" PDAs. 7,8 A compromised explanation suggests that the alkyl side chains in the "red phase" remain in an ordered conformation, with only a slightly different packing mode from the "blue phase". 31 More recent investigation of the temperature dependence of visible absorption spectra and the electron diffractions of PDA films revealed that the electronic natures of the PDAs are strongly dependent on their resonance backbone structures as well as the stacking of the main chains.…”
Section: Discussionmentioning
confidence: 99%
“…1). Amphiphilic diacetylene lipids have been polymerized to form single crystals, 4,5 Langmuir-Blodgett films, 3,[6][7][8] self-assembled monolayers, 9 and vesicles [10][11][12][13] and ribbons 14,15 in aqueous solution. Recently, immobilization of disulfide-modified PDA vesicles on gold surfaces 16 and amine-terminated vesicles on aldehyde-functionalized glass slides 17 were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Further compression of the film to 35 mN/m results in a stable film with MMA = 9 2 /molecule. It was therefore assumed that the film is organized into a trilayer superstructure [26]. Photopolymerization was carried out with a hand-held UV lamp (254 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Islands of multilayer PDA are also visible. The monolayer regions are polycrystalline, and each domain can be identified by the orientation of the striations visible in the phase image along which the PDA backbones lie [12,17]. The typical phase f in Fig.…”
mentioning
confidence: 99%